Material characteristics of historic scagliola interiors in Vienna: A view through the microscope. (15th March 2022) - Fuchs, Katharina; Pintér, Farkas
Abstract: Composition and microstructure of four Viennese scagliola samples, originating from the early 18th to early 20th centuries, were analysed by different methods of microscopy. Results indicate a similar composition in all samples; only minor differences could be observed in the porosity and grain‐size‐distribution. While, the calcium sulphate raw material was fired at low temperatures (<200°C), the presumable presence of anhydrite II in two samples may indicate hot spots (200–300°C) during the calcination. To achieve 'marble‐like' patterns mineral pigments were used to dye the ground mass. The first results show that scagliola surfaces of this study were produced by using the same or very similar technology between the 18th and early 20th centuries. The present study focuses on scagliola interiors in Vienna, Austria from different stylistic periods between the early 18th and early 20th centuries. Scagliola, also called stucco marble, imitates natural stone. It is produced by a mixture of gypsum (CaSO4 ·2H2 O), different pigments, animal glue and water. In the history of interior design, the material played an important role in the 18th and 19th centuries in Central Europe. The aim of the research was a detailed investigation of four selected samples in order to identify the raw materials and manufacturing technology of the stucco marbles used over time in Vienna. As a first step thin sections (i.e. polished, transparent samples with a thickness of 0.03 mm) were prepared from the samples and analysed by different microscopic techniques. All samples showed similarities in their bulk properties, but detailed investigations revealed also some differences in their mineralogical composition. The gypsum binders contained typical air voids and so‐called secondary pores which were formed by dissolving larger binder‐related particles during the preparation of the mixture. The macroporosity (i.e. the amount of the pores in the samples which are larger than 0.01 mm) measured on microscopic images varied in a narrow range between 14.1% and 19.3%. The raw materials of all samples were fired at relatively low temperatures (i.e. below 200°C), but in two samples we could also determine a few anhydrite (CaSO4 ) crystals that normally form at higher temperatures in the kiln. This indicates that the distribution of temperature in the kiln was heterogeneous during the firing process. The amount and appearance of some minor mineral constituents such as dolomite (CaMg[CO3 ]2 ) and celestine (SrSO4 ) suggest that they were naturally occurred in the raw material and not deliberately added to the binder as a filling material. To achieve different colour hues and imitate natural stone surfaces, fine‐grained mineral pigments and charcoal powder were used. Although we have no distinct information about the gypsum sources of these stucco marbles, several small historical gypsum quarries existed southwest of Vienna. Some of them were already in operation in the 16th century, thus a local gypsum occurrence used as a raw material is very probable. Due to the fact that the main features of the analysed samples were very similar, we assume that the scagliola surfaces of this study were produced by using the same or very similar technology between the 18th and early 20th centuries.